A Novel and Highly Regioselective Route to Construct Methylthio-Substituted Pyridazines from Aryl Methyl Ketones at Room Temperature - Wu, Liuming; Yang, Yan; Gao, Meng; Zhang, Dongxue; Shu, Wenming; Zhu, Yanping; Wu, Anxin (Synlett, 2012)
A novel and highly regioselective two-step homocoupling/cyclization procedure from easily available aryl methyl ketones and hydrazine hydrate was developed for the synthesis of methylthio-substituted pyridazines at room temperature. The method has remarkable advantages owing to the simple substrates, mild reaction conditions, ease of manipulation, good yields and high regioselectivity.
Keywords: regioselectivity; homocoupling/cyclization; aryl methyl ketones; hydrazine hydrate; methylthio-substituted pyridazine